2017
DOI: 10.1016/j.midw.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The motivation and capacity to go ‘above and beyond’: Qualitative analysis of free-text survey responses in the M@NGO randomised controlled trial of caseload midwifery

Abstract: Cite this article as: Jyai Allen, Sue Kildea, Donna L. Hartz, Mark Tracy and Sally Tracy, The motivation and capacity to go 'above and beyond': qualitative analysis of free-text survey responses in the M@NGO randomised controlled trial of caseload midwifery, Midwifery, http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 46 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…18 Models of specialist care provision have been explored with good results in areas such as twin pregnancy and birth 19 and birth after cesarean delivery. 20,21 While much work has been done on the benefits of models of continuity of caregiver provided by midwives, 22,23 less research has addressed the impact of continuity of obstetric caregiver, and trusting, stable relationships within the professional team. Continuity has been identified in qualitative research as a significant factor influencing the success of complex physiological birth, 24 and the organization of obstetric and specialist midwifery services to provide greater levels of relational continuity deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…18 Models of specialist care provision have been explored with good results in areas such as twin pregnancy and birth 19 and birth after cesarean delivery. 20,21 While much work has been done on the benefits of models of continuity of caregiver provided by midwives, 22,23 less research has addressed the impact of continuity of obstetric caregiver, and trusting, stable relationships within the professional team. Continuity has been identified in qualitative research as a significant factor influencing the success of complex physiological birth, 24 and the organization of obstetric and specialist midwifery services to provide greater levels of relational continuity deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…CMC aims to build relationships through frequent care contacts with the same midwife during a woman's care journey [12]. These relationships result in better clinical outcomes and care experiences for women [36,38,41,[44][45][46][47][48][49][50][51][52][53][54] and are thought to work through various mechanisms such as: trust [38, 47-49, 52, 53, 55]; feeling known [49,51,52,56]; feeling empowered or confident [52,53,57], feeling relaxed [52]; emotional support [45,55,58,59]; advocacy [60] and feeling safe [47]. Women in our evaluation said they liked having a relationship with their midwife, 'seeing a friendly face', feeling known and feeling confident in their midwives' abilities.…”
Section: Programme Theory 2: Relationshipsmentioning
confidence: 99%
“…Positive experience of CMC then motivates midwives and managers to engage with the opportunity to implement CMC either by volunteering or actively supporting implementation from within the wider workforce. In our study, and the literature, midwives chose to trial (or work in) CMC models, which could suggest that they might be intrinsically different to other midwives who did not put themselves forward; for example, they may have a stronger philosophical commitment to physiological pregnancy and birth or woman centred care or have different personal attributes [51,52,69]. In support of this we identified that many of the midwives who volunteered to test CMC were motivated by a lack of belief in or negative experience of the current fragmented model.…”
Section: Programme Theory 3: Midwifery Practicementioning
confidence: 99%
“…We hypothesize that the benefits of MGP over SC were primarily due to the relational component of the partnership that developed between women and their midwives across the maternity continuum [ 1 – 3 , 29 ]. Women in the MGP model had 24/7 access to a small group of known midwives and hence, had opportunities to build relationships of trust and support not possible in the SC model.…”
Section: Discussionmentioning
confidence: 99%
“…Women in the MGP model had 24/7 access to a small group of known midwives and hence, had opportunities to build relationships of trust and support not possible in the SC model. In the free text analysis of the M@NGO RCT, MGP women reported being more ‘at ease, comfortable, confident, loved, reassured, relaxed, safe, and supported’ in this model of care compared to women in SC models [ 29 ]. The home visits up to 6-weeks postnatally may have also played an important role in supporting women’s transitions to motherhood.…”
Section: Discussionmentioning
confidence: 99%